2011
DOI: 10.3390/ijms12010173
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Photovoltaics in Nanoscale Dimension

Abstract: This review focuses on the intrinsic charge transport in organic photovoltaic (PVC) devices and field-effect transistors (SAM-OFETs) fabricated by vapor phase molecular self-assembly (VP-SAM) method. The dynamics of charge transport are determined and used to clarify a transport mechanism. The 1,4,5,8-naphthalene-tetracarboxylic diphenylimide (NTCDI) SAM devices provide a useful tool to study the fundamentals of polaronic transport at organic surfaces and to discuss the performance of organic photovoltaic devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 117 publications
0
9
0
Order By: Relevance
“…The free monomers exhibit a typical vibronic structure between 300 and 400 nm. , Depending on the solvent, there is a broad absorption band beyond 400 nm (see inset in Figure ). This band is the signature of the presence of π-oligomers in the solution and compares well with many other perylene diimide derivatives. , Recent calculations and experimental data have confirmed the important redshift due to the aggregation . The concentration of π-aggregated molecules is the largest in BD and the lowest in DMSO.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The free monomers exhibit a typical vibronic structure between 300 and 400 nm. , Depending on the solvent, there is a broad absorption band beyond 400 nm (see inset in Figure ). This band is the signature of the presence of π-oligomers in the solution and compares well with many other perylene diimide derivatives. , Recent calculations and experimental data have confirmed the important redshift due to the aggregation . The concentration of π-aggregated molecules is the largest in BD and the lowest in DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…This band is the signature of the presence of π-oligomers in the solution and compares well with many other perylene diimide derivatives. 25,26 Recent calculations 27 and experimental data 28 have confirmed the important redshift due to the aggregation. 27 The concentration of πaggregated molecules is the largest in BD and the lowest in DMSO.…”
Section: ■ Experimental Sectionmentioning
confidence: 88%
“…Kaake et al measure ATR-IR spectrum of PTCDI lm and found the C]O symmetric and asymmetric bands at 1696 and 1655 cm À1 , respectively. 78 Measuring NTCDI lms FT-IR spectrum, Burtman et al 30 observed an important shi from 1779 to 1655 cm À1 for n C]O . These observations are in a good agreement with recent results obtained for PTCDI molecules by DFT calculations at B3LYP/6-31G* level.…”
Section: Infrared Spectroscopy Analysismentioning
confidence: 99%
“…in the eld of solar cell energy conversion. [28][29][30] Later, the self-organization of molecules was studied under ultrahigh vacuum, nowadays, new methods have been developed to investigate also the solid-liquid interface. 21,22 These methods have the advantage, not only to manipulate the molecules in the air, but also to achieve a phase discrimination as a function of their relative stability.…”
Section: Introductionmentioning
confidence: 99%
“…20−24 However, there exists little work on solid state devices based on photoresponsive monolayers. 25,26 Here we demonstrate the possibility of fabricating a solid state light sensitive molecular junction that allows the measurement of a photocurrent generated by the light absorption of a molecular monolayer. In 1980, Kuhn et al 27,28 showed the photocurrent extraction from a sandwich structure composed of alternate layers of donor and acceptor molecules.…”
Section: ■ Introductionmentioning
confidence: 99%